Tax Revenue Instability in Sub-Saharan Africa: Consequences and Remedies - (:unkn) unknown (My University, 2012)
This paper focuses on the sources and consequences of the instability of tax revenue in Sub-Saharan African countries. We took advantage of a unique and extraordinarily rich data set on the composition of tax revenues for a large number of countries. Using panel data for thirty-seven countries observed over the period 1980-2005, we find that our results are twofold. First, the instability of government tax revenue leads to the instability of both public investment and government consumption and also reduces the level of public investment. Second, the reliance on domestic indirect taxation-based systems appears to have a robust stabilising effect.
Keywords: African Research